Physical Exercise and the Renin Angiotensin System: Prospects in the COVID-19 - Evangelista, Fabiana S. (Frontiers in Physiology, 2020)
Recent reports have shown that the renin angiotensin system (RAS) plays an important role in the Coronavirus disease 2019 (COVID-19) because the angiotensin converting enzyme 2 (ACE2) is the receptor for the severe acute respiratory syndrome (SARS) coronavirus 2 (SARS-CoV)-2. In addition, the balance of RAS components can be involved in the pathogenesis and progression of COVID-19, especially in patients with metabolic and cardiovascular diseases. On the other hand, physical exercise (PE) is effective to prevent and to counteract the consequences of such diseases and one of the biological mediators of the exercise adaptation is the RAS. This review was designed to highlight the connection between COVID-19 and RAS, and to discuss the health-related aspects of PE and the role of the RAS.